Bolshevik opposition to the idea of the turkic unity (the first quarter of the twentieth century) (Journal of history, 2021)
The article discusses the emergence of the idea of the unification of Turkic peoples in the early twentieth century, as well as V. Lenin’s and J. Stalin’s position on national autonomy, unification on the cultural and national basis, the issues of the nation and the ways, the stages of its realization, the fight of the Bolsheviks against Turkic unity.In addition, the article describes how, after the formation of the USSR in December 1922, the People’s Commissariat for Nationalities, headed by Stalin, began to actively determine the direction and how to address the issue of nationalities in the national republics and oblasts.To study one of the most complex and controversial periods in the history of the former USSR, the author was guided by the principle of historicism, considering processes and phenomena in causal, temporal contact. The use of the problem-chronological method made it possible to create material in a chronological sequence, as well as to highlight important patterns and trends. The following methods were used: historical-genetic, historical-comparative, and historical-systemic methods as specific meth- ods of historical research. The study, based on archival data and the works of the intelligentsia of the Turkic nations, presents information about the Turkic movement in Russia in the first quarter of the 20th century.Key words: Turkic unity, Alashorda, nationalism, Bolshevik, V. Lenin, J. Stalin, Soviet period.